2017
DOI: 10.1097/jom.0000000000001026
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Bullying as a Predictor of Disability Retirement

Abstract: Objective:The aim of this study was to determine 1) whether bullying is related to all-cause disability retirement, 2) whether bullying contributes to the variance in disability retirement above high job demands and lack of job control, and 3) to establish gender differences in the relationship.Methods:Survey data from 14,501 Norwegian employees on exposure factors linked to registry data on all-cause disability retirement.Results:Bullying significantly predicted risk of disability retirement (hazard ratio = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 28 publications
1
14
0
1
Order By: Relevance
“…Increased health risks and even morbidity have been linked to workplace bullying (Khubchandani & Price, ). In a survey study of 14,501 employees from Norway, researchers Nielsen, Emberland, and Knardahl () found that workplace bullying predicted a significant risk of disability and that women were more at risk of disability than men.…”
Section: Review Of the Relevant Literaturementioning
confidence: 99%
“…Increased health risks and even morbidity have been linked to workplace bullying (Khubchandani & Price, ). In a survey study of 14,501 employees from Norway, researchers Nielsen, Emberland, and Knardahl () found that workplace bullying predicted a significant risk of disability and that women were more at risk of disability than men.…”
Section: Review Of the Relevant Literaturementioning
confidence: 99%
“…In his theorized process model, workplace bullying is construed as a gradually evolving phenomenon starting with low-intensity conflicts or incivility, and ending with the target's exclusion from the workplace or from working life itself, if victimization is allowed to escalate and management fails to adequately intervene (see Leymann, 1990Leymann, , 1992. However, thorough empirical support for the assumption of Leymann has only been presented more recently, showing for instance that workplace bullying can predict long-term sickness absence, working disability and unemployment (Glambek, Skogstad, & Einarsen, 2015;Hogh, Hoel, & Carneiro, 2011;Niedhammer, Chastang, Sultan-Taïeb, Vermeylen, & Parent-Thirion, 2013;Nielsen, Emberland, & Knardahl, 2017).…”
Section: Workplace Bullying and Risk Of Exclusionmentioning
confidence: 99%
“…Their findings showed that exposure to bullying increased the duration of the absence among women, but not among men. However, due to the strong effects of bullying on both subsequent health complaints (Kivimäki et al., 2003; Finne et al., 2011; Xu et al., 2018a,b) and risk of disability retirement (Nielsen et al., 2017b), an association between bullying and the duration of absence seems reasonable. As a replication and extension of previous research on workplace bullying and sickness absence, this study will examine the impact of exposure to bullying on both the risk and the duration of sickness absence.…”
Section: Bullying and Sickness Absencementioning
confidence: 99%
“…Hence, workplace bullying is not about single episodes of conflict or harassment at the workplace, but a form of persistent abuse where the exposed employee is unable to withstand or cope with the mistreatment (Einarsen, 1999; Einarsen et al., 2011). Both longitudinal studies and meta-analyses have established workplace bullying as a significant risk factor for health outcomes such as anxiety and depression (Nielsen and Einarsen, 2012; Verkuil et al., 2015), somatic complaints (Hoobler et al., 2010; Kääriä et al., 2012; Tynes et al., 2013), cardiovascular disease (Xu et al., 2018a,b), diabetes (Xu et al., 2018a,b), and disability retirement (Nielsen et al., 2017b). Comparisons with other psychosocial exposures show that bullying is one of the most detrimental predictors of health problems (Schutte et al., 2014).…”
mentioning
confidence: 99%